2019
DOI: 10.1093/jxb/erz394
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing 3D inflorescence architecture in grapevine using X-ray imaging and advanced morphometrics: implications for understanding cluster density

Abstract: Grapevine 3D inflorescence architecture was comprehensively characterized among 10 wild Vitis species to reveal new phenotypic and evolutionary relationships.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 81 publications
0
32
0
Order By: Relevance
“…Although the processing and analysis of 3D images for complex biological structures remains nontrivial, automated computational tools providing precise analysis for 3D imaging are becoming increasingly powerful, permitting segmentation, reconstruction, registration, visualization, feature extraction, and modeling. For example, 3D wheat grains have been segmented and measured from images of the wheat panicle (Hughes et al , 2017), and 3D branching topology has been characterized comprehensively in grapevine inflorescences (Li et al , 2017, 2019). Furthermore, software such as C himera (Pettersen et al , 2004) has been used widely for the visualization and analysis of molecular structures, density maps, 3D microscopy, and associated data (Goddard et al , 2017), and topological data analysis tools such as the medial axis (Blum, 1967) have been used extensively for analyzing shape structure and for forming shape descriptors.…”
Section: Introductionmentioning
confidence: 99%
“…Although the processing and analysis of 3D images for complex biological structures remains nontrivial, automated computational tools providing precise analysis for 3D imaging are becoming increasingly powerful, permitting segmentation, reconstruction, registration, visualization, feature extraction, and modeling. For example, 3D wheat grains have been segmented and measured from images of the wheat panicle (Hughes et al , 2017), and 3D branching topology has been characterized comprehensively in grapevine inflorescences (Li et al , 2017, 2019). Furthermore, software such as C himera (Pettersen et al , 2004) has been used widely for the visualization and analysis of molecular structures, density maps, 3D microscopy, and associated data (Goddard et al , 2017), and topological data analysis tools such as the medial axis (Blum, 1967) have been used extensively for analyzing shape structure and for forming shape descriptors.…”
Section: Introductionmentioning
confidence: 99%
“…This method was also used in nuts and few works are reported, such as the detection of pinhole insect damage in almonds [ 46 ], the segmentation and classification in hazelnuts [ 47 ] and the behaviour study of fourth-instar weevil in pecan nuts [ 48 ]. In grapevine, a recent study aimed to characterize inflorescence architecture using X-rays [ 49 ]. The authors found correlations between 24 morphological traits among 392 samples of 10 wild Vitis species.…”
Section: Introductionmentioning
confidence: 99%
“…Bunch architecture is controlled by environmental and genetic factors (Döring et al 2015 ; Tello and Ibáñez 2017 ). It is a complex trait composed of berry and stalk characteristics (Li et al 2019 ; Richter et al 2019 ; Rist et al 2018 ). Some of these sub-traits are under genetic control as reported for berry size, berry volume and berry weight (Ban et al 2016 ; Houel et al 2015 ; Mejia et al 2007 ; Tello et al 2015 ), berry number (Dry et al 2010 ; Fanizza et al 2005 ) and other rachis sub-traits (Correa et al 2014 ; Marguerit et al 2009 ; Tello et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%